Applications of artificial intelligence in Islamic thought - Noor Awad Khalaf (Islamic Sciences Journal, 2026)
The research addresses the role of artificial intelligence applications in Islamic thought, reviewing the legal foundations of artificial intelligence, the concept of sustainable development from an Islamic perspective, applications in Islamic fields, and its challenges and future prospects. He concluded that Islam supports science and the discovery of what benefits humanity, while giving priority to divine sciences and strengthening the relationship between the servant and his Lord, without clashing with modern technology. The study emphasized the importance of a comprehensive jurisprudential approach to assessing the legitimacy of using artificial intelligence according to the obligatory rulings, classifying it as a human need rather than a necessity, which requires expert evaluation to determine its importance in different contexts.